Ten years of interfaculty pain curriculum at the University of Toronto: impact on student learning. (30th November 2021) - Cioffi, Iacopo; Dale, Craig M.; Murphy, Laura; Langlois, Sylvia; Musa, Renata; Stevens, Bonnie
Abstract : Supplemental Digital Content is Available in the Text. The University of Toronto Interfaculty Pain Curriculum has significantly improved students' pain knowledge and ability to develop interprofessional care plans over the period 2009 to 2019. Abstract: Introduction: Delivery of interprofessional pain education for prelicensure healthcare professionals is strongly recommended to advance a workforce ready for collaborative practice and to improve the quality and outcomes of pain care. Objectives: We report a 10-year (2009–2019) longitudinal evaluation of a 20-hour undergraduate Interfaculty Pain Curriculum (IPC) delivered to students in the Faculties of Dentistry, Nursing, Pharmacy, and Medicine (also including the Departments of Physical Therapy, Occupational Therapy and Physician Assistant) at the University of Toronto, Canada. The IPC follows a constructivist approach to facilitate interactive and multifaceted learning. Methods: Evaluation methods based on the Kirkpatrick model were used to appraise changes in participating students' pain knowledge and beliefs and their ability to collaboratively develop an interprofessional pain management plan. Results: A total of 10, 693 students participated over the 10-year study period. The mean annual attendance was 972 students and participation to the program increased significantly over the years. Overall, the IPC was effective in improving students' mean pain knowledge and beliefs scores; however, the mean knowledge score gains were negatively correlated with time, likely related to increased uniprofessional pain education. Although an increasing trend in mean interprofessional pain management plan scores was observed, the scores were not significantly correlated with time. Conclusions: The interactive and multifaceted IPC is consistently effective in improving knowledge and beliefs and interprofessional pain management care plan development among participating student cohorts. Future inquiry is required to better understand the mechanisms behind student learning in interprofessional pain education to enhance pain curriculum development and delivery.